The Use of a Jigsaw-Type Cooperative Learning Model to Improve Reading Skills in Grade VIII Students of MTs Al-Irfan Tanjungsari Sumedang - Ade Nandang; Ade Arip Ardiansyah; Delia Dwi Putri (Gunung Djati Conference Series, 2025)
Eighth-grade students at MTs Al-Irfan Tanjungsari Sumedang are facing low reading skills in Arabic language lessons. This issue is caused by the conventional, teacher-centered teaching methods, which result in students being less active in the learning process. This study aims to determine how the jigsaw cooperative learning model is applied to improve the students' reading skills and whether this model can enhance their reading abilities. This research is a Classroom Action Research (CAR) of a descriptive nature. The data was collected from the Arabic language teacher as the research subject and the eighth-grade students as the research objects, using tests, observations, and documents for data collection. The data analysis method in this study used percentages. The results showed that after using the Cooperative Learning Model of the Jigsaw type, students' reading skills improved, reaching the Minimum Competency Criteria (KKM). In the first cycle, students' reading skills reached 50%, and in the second cycle, it increased to 80%. From these results, it can be concluded that there is an improvement in students' reading skills using the Cooperative Learning Model of the Jigsaw type.